Bone-Marrow-Derived Cells Contribute to Glomerular Endothelial Repair in Experimental Glomerulonephritis - Rookmaaker, Maarten B. (American Society for Investigative Pathology, 2003)
Glomerular endothelial injury plays an important role in the pathogenesis of renal diseases and is centrally involved in renal disease progression. Glomerular endothelial repair may help maintain renal function. We examined whether bone-marrow (BM)-derived cells contribute to glomerular repair. A rat allogenic BM transplant model was used to allow tracing of BM-derived cells using a donor major histocompatibility complex class-I specific mAb. In glomeruli of chimeric rats we identified a small number of donor-BM-derived endothelial and mesangial cells, which increased in a time-dependent manner. Induction of anti-Thy-1.1-glomerulonephritis (transient mesangial and secondary glomerular endothelial injury) caused a significant, more than fourfold increase in the number of BM-derived glomerular endothelial cells at day 7 after anti-Thy-1.1 injection compared to chimeric rats without glomerular injury. The level of BM-derived endothelial cells remained high at day 28. We also observed a more than sevenfold increase in the number of BM-derived mesangial cells at day 28. BM-derived endothelial and mesangial cells were fully integrated in the glomerular structure. Our data show that BM-derived cells participate in glomerular endothelial and mesangial cell turnover and contribute to microvascular repair. These findings provide novel insights into the pathogenesis of renal disease and suggest a potential role for stem cell therapy.